Factorial analysis on nitrogen, phosphorus and potassium contents in mushroom waste - Muhammad Faiz, Mohamed Ameen (2016)
The potential of Grey Oyster Mushroom (Pleurotus spp.,) mushroom waste (MW) as bio-fertilizer was investigated in this study. The agriculture industry relies heavily on the use of bio-fertilizer and the main components in bio-fertilizer was nitrogen (N), phosphorous (P), and potassium (K). Thus, a study was conducted to identify the N, P and K content in the MW. These N, P and K were numerous building blocks of life that plants need for healthy growth. Thus, by increasing the N, P and K content in MW, it can be utilized to produce high and better quality of bio-fertilizer. Five independent factors, i.e. aging of waste (fresh 0 days/ aged 14 days), waste pH (7-8.5), composition (MW only/ mixture of MW & spent medium (SM)), technique of drying (oven 50oc/ sunlight) and MW size (powder/ cut) were the affecting processing factors on N, P and K content in MW. Design Expert software (Version 7) was used to construct experimental table where all the factors was randomized. The most contributing factor and interaction between the factors was analyzed via two level factorial analysis by using the same software. The chemical components of interest in this study were N, P, and K have measured using HACH Spectrophotometer. The outcome of this research was to identify the best combination of processing factors. Some of the independent factors were shown to have a significant effect on the N, P and K content. The results showed that the most significant factor in N content: MW size and aging of waste while for P and K content: technique of drying and MW size. The best condition was identified to maximize the amount of N, P and K content in MW. The identified conditions were the MW aged for 7 days, MW size at powder form, waste pH at 7, dry under sun light and the composition MW only. The results show that fractional factorial design was suitable in investigating the effect of factors with a minimum number of experiments. Based on proposed condition the ratio of N, P and K content was 4-1-3. The predicted result was compared with the reported experimental result with error of 9.57% for N, 0.92% for P and 2.93% for K.